Experimentally Manipulating Items Informs on the (Limited) Construct and Criterion Validity of the Humor Styles Questionnaire - Ruch, Willibald; Heintz, Sonja (Frontiers in Psychology, 2017)
How strongly does humor (i.e., the construct-relevant content) in the Humor Styles Questionnaire (HSQ; Martin et al., 2003) determine the responses to this measure (i.e., construct validity)? Also, how much does humor influence the relationships of the four HSQ scales, namely affiliative, self-enhancing, aggressive, and self-defeating, with personality traits and subjective well-being (i.e., criterion validity)? The present paper answers these two questions by experimentally manipulating the 32 items of the HSQ to only (or mostly) contain humor (i.e., construct-relevant content) or to substitute the humor content with non-humorous alternatives (i.e., only assessing construct-irrelevant context). Study 1 (N = 187) showed that the HSQ affiliative scale was mainly determined by humor, self-enhancing and aggressive were determined by both humor and non-humorous context, and self-defeating was primarily determined by the context. This suggests that humor is not the primary source of the variance in three of the HQS scales, thereby limiting their construct validity. Study 2 (N = 261) showed that the relationships of the HSQ scales to the Big Five personality traits and subjective well-being (positive affect, negative affect, and life satisfaction) were consistently reduced (personality) or vanished (subjective well-being) when the non-humorous contexts in the HSQ items were controlled for. For the HSQ self-defeating scale, the pattern of relationships to personality was also altered, supporting an positive rather than a negative view of the humor in this humor style. The present findings thus call for a reevaluation of the role that humor plays in the HSQ (construct validity) and in the relationships to personality and well-being (criterion validity).